2018
DOI: 10.1002/slct.201800487
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Anticancer Acenaphtho[1, 2‐b]quinoxaline: Green Synthesis, DFT and Molecular Docking Studies, Live‐Cell Imaging and Reactivity towards Nucleic Acid and Protein BSA

Abstract: A series of acenaphtho[1, 2‐b]quinoxaline derivatives 3 a‐3 j were prepared using single step condensation of acenaphthoquinone with different o‐phenylene diamine derivatives on water under sonication. Interaction of 9‐fluoro acenaptho[1, 2‐b]quinoxaline (3 g) with calf‐thymus DNA has been explored by using absorption and emission techniques. The compound 3 g cleave DNA oxidatively without any exogenous additives. The protein binding ability has been observed by quenching of tryptophan emission in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In this contribution we are making a point to achieve excellent yields, higher atom economy, and one pot synthesis to reduce the reaction steps, use of water as a green solvent, and implementation of ultrasonic irradiation to avoid hazardous reaction conditions, to develop a more energy efficient synthetic route. 23,24 The photodynamic effect is basically the harm or damage of living cells or tissues by visible light in the presence of a photosensitizer and oxygen. 25,26 The mechanism of PDT is really fascinating and it consists of two types, Type-I which leads to the formation of a superoxide or a hydroperoxyl radical (HO 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this contribution we are making a point to achieve excellent yields, higher atom economy, and one pot synthesis to reduce the reaction steps, use of water as a green solvent, and implementation of ultrasonic irradiation to avoid hazardous reaction conditions, to develop a more energy efficient synthetic route. 23,24 The photodynamic effect is basically the harm or damage of living cells or tissues by visible light in the presence of a photosensitizer and oxygen. 25,26 The mechanism of PDT is really fascinating and it consists of two types, Type-I which leads to the formation of a superoxide or a hydroperoxyl radical (HO 2…”
Section: Introductionmentioning
confidence: 99%
“…In this contribution we are making a point to achieve excellent yields, higher atom economy, and one pot synthesis to reduce the reaction steps, use of water as a green solvent, and implementation of ultrasonic irradiation to avoid hazardous reaction conditions, to develop a more energy efficient synthetic route. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al 46 reported an environmentally friendly method for the synthesis of novel spiro-2-amino-3-phenylsulfonyl-4H-pyran derivatives 91 in 88-94% yields in EtOH with a novel basic ionic liquid, 2-hydroxyethylammonium acetate [H 3 N + CH 2 CH 2 OH][AcO -] (HEAA), as the catalyst in the multicomponent reaction of phenylsulfonylacetonitrile (92) and 1,3-dicarbonyl compounds 90c-f,k with 1 (Scheme 32). The 1,3-dipolar cycloaddition reaction of 2-oxo-(2H)acenaphthylen-1-ylidene-malononitrile (72) as the dipolarophile has been reported with azomethine ylides generated in situ from N-substituted isatins 93 and sarcosine (2) for the synthesis of novel dispiropyrrolidine oxindole derivatives 94 in 73-79% yields (Scheme 33).…”
Section: Scheme 31 Synthesis Of Spiroacenaphthylene-pyran Derivatives 89mentioning
confidence: 99%
“…Some of the synthesized derivatives exhibited cytotoxic activity. 92 Scheme 66 Synthesis of arylquinoxaline derivatives 188 using a metal catalyst 2-Oxindolyl-2-hydroxyacenaphthylen-1-ones 190 were synthesized in 81-88% yields by a one-pot, three-component reaction of 3-diazooxindole 191, benzyl alcohol derivatives (192) and 1 in the presence of rhodium(II) acetate (1 mol%) as the catalyst with high chemo-and diastereoselectivity (Scheme 67). Antibacterial activities of the synthesized oxindoles and group-based quantitative structure-activity relationships (GQSAR) for all antibacterial activities were evaluated.…”
Section: Review Syn Thesismentioning
confidence: 99%
“…Moreover, intercalation can result in signicant changes to the length of the DNA helix, stiffness and unwinding that have powerful impacts on DNA replication and transcription. 46,47 Human serum albumin (HSA, 66.5 kDa) is the most prevalent protein in human plasma; it binds with various ligands associated with metal complexes at various locations, and it plays a vital role in the transport and control over the bioactivity of titanium(IV) derivatives, including cytotoxic drugs. The binding interaction of BSA (75% sequence identity with HSA) with derivatives of titanium(IV) facilitates determination of the affinity constant and primary coordination sites.…”
Section: Introductionmentioning
confidence: 99%